Strategi Bimbingan Karier Melalui Pengembangan Kreativitas Siswa Dengan Retardasi Mental Di SMA Al-Firdaus Sukoharjo - Siti Hidayatun Nafiah; Alfin Miftahul Khairi (Academic Journal of Psychology and Counseling, 2022)
Students with intellectual disability require career guidance to develop their creativity and potential. This research aimed to describe teacher career guidance strategies in developing the creativity of students with intellectual disability at SMA Al Firdaus Sukoharjo. The study used a qualitative approach with the case study method. Research participants consisted of guidance and counseling (BK) teachers, inclusion coordinators, and two accompanying teachers. Data were collected via observation, interviews, and documentation. Researchers implemented the Miles and Huberman theory for the data analysis, which involves data reduction, data display, and conclusion drawing. The results show that the strategies used for career guidance are instructional (teaching methods) and substantial (interpersonal relationships). With these strategies, teachers can inspire mentally retarded students to develop their talent and interests. In addition, teachers pay attention to emotional closeness, namely by giving creative freedom to students. It was noted that there were mentally retarded students who won at the national level and there were alumni who had businesses after they graduated.